Electric Vehicles and Storage Systems Integrated within a Sustainable Urban District Fed by Solar Energy. (12th December 2019) - Bracco, Stefano; Delfino, Federico; Longo, Michela; Siri, Silvia
Abstract : In this paper, an optimization model is defined for the design of a smart energy infrastructure integrating different technologies to satisfy the electrical demand of a given site. The considered smart energy infrastructure includes a photovoltaic plant, electrical storage systems, electric vehicles (EVs), and charging stations. The objective function of the optimization model considers the costs related to the installation and maintenance of the considered technologies, as well as the costs associated with the energy exchanges with the external grid. A very extensive numerical analysis is reported in the paper, referred to a test case in a real site in Liguria Region, in the north of Italy. Many scenarios are analyzed and discussed, with specific attention to evaluate the role of electric mobility within a smart energy infrastructure and a focus on EVs acting as mobile storage systems.